ENHANCED ADSORPTIVE REMOVAL OF HEXAVALENT CHROMIUM USING ALIQUAT-336 IMPREGNATED CHITOSAN–GRAPHENE OXIDE BEADS: ISOTHERM AND KINETIC STUDIES - M. D. Bansinge; P. V. Tekade (International Journal of Research -GRANTHAALAYAH, 2025)
Aliquat-336 impregnated chitosan-graphene oxide (CHGOAL) was developed and tested as efficient adsorbents to facilitate the removal of hexavalent chromium (Cr(VI)) from aqueous media. The composite was a hybrid of the extensive surface area and oxygen-rich functional moieties present on graphene oxide and the amino groups of chitosan and the quaternary ammonium sites of Aliquat-336 which increased the adsorption performance. FTTIR characterization was used to verify interactions between components and XRD was used to show an amorphous structure with dispersed graphene oxide. The impact of the pH, the dosage of the adsorbent, contact time, and the initial concentration of Cr(VI) were analyzed by batch adsorption experiments. The equilibrium adsorption capacity of the adsorbent as per the Langmuir model was 191.36 mg g-1 and was at pH 3 which had the maximum removal. The pseudo-second-order model was appropriate to fit kinetic data (R2=0.998) demonstrating that chemisorption constituted the rate-limiting step. The CHGOAL beads proved to have high removal efficiency, structural stability, and also reusability which is a good indication of their great application in industrial wastewater treatment and environmental remediation.